A feeling for the (micro)organism? Yeastiness, organism agnosticism and whole genome synthesis. Issue 4 (1st October 2020) - Calvert, Jane; Szymanski, Erika
Abstract : Synthetic biologists attempt to apply engineering principles to biological systems. This involves treating organisms as "chassis" – neutral frames into which synthetic constructs can be inserted, rather than living entities with distinctive features. Here we focus on a particularly charismatic organism – Saccharomyces cerevisiae (brewer's yeast) – and the attempt to make a synthetic version of its genome. We argue that the "personality" of the yeast and the affective relationship scientists (and others) have to it, challenges the "organism agnosticism" of synthetic biology. This leads us to ask whether synthetic biologists have straightforwardly exploitative relationships to the organisms they work on. We connect this "feeling for the (micro)organism" to the activity of engineering whole genomes, rather than discrete genetic parts. We argue that this connection is significant because we are likely to see an escalation in attempts to synthesize complete genomes in the future, including the human genome.